Halal Lifestyle During The COVID-19 Pandemic - Rahman, Miftahur; Roqib, Moh.; Khotimah, Khusnul; Ahmad, Norhafizah (Advances in Humanities and Contemporary Studies, 2024)
Many people began to show interest in the concept and understanding of the halal lifestyle in their daily lives. Halal food is the biggest concern today; not only packaged food but food in restaurants is also a lot of spotlight on halal. Not only food, hotel facilities, banking services, socialization, traveling, toiletries, health supplies, cosmetics, etc. Halal occupies the interests of producers, customers, stakeholders, and entrepreneurs. All these aspects of life are inseparable from the regular activities of a Muslim. The term halal lifestyle, in general, has not been established but explicitly but implicitly mentioned in the Qur’an and hadith. When halal-oriented goods and services are offered, ultimately, the halal lifestyle will become a privilege for Muslims. This study presents an overview of the term halal lifestyle and how to direct the potential of halal lifestyle in everyday life. Also, challenges that occur and will occur later when the halal lifestyle is implemented. The halal lifestyle is something that brings comfort and security to the community itself.